Anxiety and Its Influencing Factors in Patients With Drug-Induced Liver Injury - Liu, Yi-Hui; Guo, Yan; Xu, Hong; Feng, Hui; Chen, Dong-Ya (Frontiers in Psychology, 2022)
Objective: This study aims to investigate anxiety and its influencing factors in patients with drug-induced liver injury (DILI). Method: Ninety-four patients with DILI were enrolled and evaluated with a self-rating anxiety scale (SAS). According to the anxiety score, they were divided into four groups: the non-anxiety, mild anxiety, moderate anxiety, or severe anxiety groups, and the scores were analyzed based on demographic and biochemical indicators. Results: Of the 94 patients with DILI, 63 did not have anxiety and 31 had anxiety (32.9%), of which 27 had mild, 3 had moderate, and 1 had severe anxiety. There were no statistically significant differences in gender, age, occupation, and level of education between the groups (F = 1.42, H = 2.361, H = 6.751, H = 1.796, and P > 0.05); anxiety score and degree of anxiety between the types of drugs that led to the liver injury (H = 0.812, H = 1.712, and P > 0.05); anxiety score between the different degrees of liver injury (H = 2.836, H = 4.957, P > 0.05); or length of hospital stay or prognosis between the degrees of anxiety (F = 1.487, H = 0.761, P > 0.05). However, there were statistically significant differences in the degree of anxiety between different degree and types of liver injury (H = 7.981, H = 8.208, P < 0.05). Conclusion: Patients with DILI may have anxiety, especially mild anxiety. The occurrence of anxiety in patients with DILI is not related to gender, age, occupation, or level of education but may be related to the degree and type of liver injury. Anxiety has no impact on the length of stay in hospital or the prognosis of the DILI. These findings may contribute to the development of management strategies for patients with DILI.